The Candida albicans exotoxin Candidalysin promotes alcohol-associated liver disease - Chu, Huikuan (J Hepatol, 2019)
BACKGROUND AND AIMS: Alcohol-associated liver disease is a leading indication for liver transplantation and leading cause of mortality. Alterations of the gut microbiota contribute to pathogenesis of alcohol-associated liver disease. Patients with alcohol-associated liver disease have increased proportions of Candida spp. in the fecal mycobiome. However, little is known about the effect of intestinal Candida on alcohol-associated liver disease. Here we evaluated the contributions of Candida albicans and its exotoxin Candidalysin on alcoholic liver disease. METHODS: C. albicans and ECE1 were analyzed in fecal samples from controls, patients with alcohol use disorder and alcoholic hepatitis. Mice colonized with different and genetically manipulated C. albicans strains were subjected to the chronic-plus-binge ethanol diet model. Primary hepatocytes were isolated and incubated with Candidalysin. RESULTS: The percentages of subjects carrying ECE1 are 0%, 4.76% and 30.77% in non-alcoholic controls, alcohol use disorder patients and alcoholic hepatitis patients, respectively. Candidalysin exacerbates ethanol-induced liver disease and is associated with increased mortality in mice. Candidalysin enhances ethanol-induced liver disease independent of the β-glucan receptor CLEC7A on bone-marrow derived cells, and Candidalysin does not alter gut barrier function. Candidalysin can damage primary hepatocytes in a dose-dependent manner in vitro and is associated with liver disease severity and mortality in patients with alcoholic hepatitis. CONCLUSIONS: Candidalysin is associated with progression of ethanol-induced liver disease in preclinical models and worse clinical outcomes in patients with alcoholic hepatitis.